Reductive Amination of Aryl Boronic Acids: Parallelism of the Catalytic Reactivity of Transition Metals and Main Group Elements in the C(sp2)–N Bond-Forming Reactions - Levitskiy, Oleg A.; Magdesieva, Tatiana V. (Synthesis, 2020)
The results of the DFT studies on the mechanism of the PIII/PV=O catalyzed reductive amination of nitrosoarenes using ArB(OH)2 yielding diaryl amines are reported. This allowed a comparison of the reaction paths and key intermediates of the Cu(I)- and P(III)-mediated reductive aminations of aryl boronic acids using alkylnitrites, nitroso- or nitroarenes, and revealed important similarities in the catalytic reactivity of transition-metal and main-group elements in C(sp2)–N bond-forming reactions. It is shown that both transformations occur via ambiphilic nitrenoid-type key intermediates, the reactivity of which towards the aryl boronic acid is attributed to the presence of both a Lewis acid center (Cu or P) and a Lewis base center (the N or O atoms of the ‘N=O’ component).
Keywords: C–N coupling; nitrenoids; diarylamines; main group catalysis; transition metal catalysis